PENGARUH KEGIATAN PLANTING IN POTS TERHADAP LITERASI SAINS ANAK USIA 4-5 TAHUN - Ferreira Mulya Fasha; Mallevi Agustin Ningrum; Eka Cahya Maulidiyah; Kartika Rinakit Adhe (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of planting in pots activities on the scientific literacy of children aged 4-5 years in Smart School Kindergarten. The approach used is a quantitative method with a pre-experimental design. Pre-experimental uses a one group pretest-posttest model. The subjects of this study consisted of 17 children in group A. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques used the Wilcoxon signed-rank test. Based on the results of the data analysis, the Z value was obtained at -3.741b with an Asymp, Sig. (2-tailed) value of 0.000. The significance value is smaller than the specified significance level of 0.05 (0.000 <0.05). So, it can be concluded that there is an effect of planting in pots activities on the scientific literacy of children aged 4-5 years in Smart School Kindergarten.